The Self-Identifications Through Pronominal Choice in Turkish Political Discourse - Candarli, Duygu (Richtmann Publishing, 2012)
Political discourse studies have analyzed the context and the way that personal pronouns and possessive pronouns are usedby politicians and how they maintain their stance through their conversations in different contexts (Van Dijk, 1997, 2002). This studyattempts to examine self-identifications that Turkish political party leaders develop through their employment of pronominal choice. Thedata come from the period before 2011 elections in Turkey. By comparing their first person singular and plural possessive pronoun usein different contexts, this paper tries to find out the factors that affect the distribution of their pronominal choice in Turkish politicaldiscourse. Within the critical discourse analysis approach, the results indicate that the location, topic, purpose and venue influence thepronominal choice of the politicians.